GENDERED SPEECH COMMUNICATION (American Journal of Interdisciplinary Research and Development, 2022)
The Communication can be viewed as a microcosm of social behavior. Much of human interaction occurs at the linguistic level. The content of the article is dealt with, the speech of the feminine and masculine and their differences. A tentative style of speaking supports women's general desire to create equality and include others. It is important to realize, however, that people outside of women's speech community may misinterpret women's intentions in using tentative communication.  In interaction with women, who have learned to demonstrate interest more vigorously, minimal response cues generally inhibit conversation because they are perceived as indicating lack of involvement.